1998
DOI: 10.1063/1.121512
|View full text |Cite
|
Sign up to set email alerts
|

Disorder effects in epitaxial thin films of (La,Ca)MnO3

Abstract: We have investigated as-grown sputtered films of La0.7Ca0.3MnO3 in a thickness range between 5 and 200 nm on SrTiO3 substrates. The films are epitaxial, strained, and smooth. All films order magnetically around 175 K. Very thin films show full magnetization at low temperatures, but the temperature of the metal–insulator transition is appreciably lower than the magnetic ordering temperature. In thick films, the magnetization is much lower than expected. Both effects are probably related to structural disorder a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 15 publications
8
70
0
Order By: Relevance
“…However, Aarts et al [13] reported that the type of oriented domains is dependant on the film thickness. As the film thickness increased from 5nm to more than 30nm, the microstructure of films turned from pure [001] oriented from mixed domains of…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Aarts et al [13] reported that the type of oriented domains is dependant on the film thickness. As the film thickness increased from 5nm to more than 30nm, the microstructure of films turned from pure [001] oriented from mixed domains of…”
Section: Discussionmentioning
confidence: 99%
“…So the columnar grain size is larger in the film deposited at 1073K than at 873K, which is consistent with the results reported by Wang et al [11,12]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 The formation of oriented domains of Pnma structure has been largely reported not only in La 1-x R x MnO 3 (R= Ca, Sr or vacancy) thin films [13][14][15][16][17][18][19][20][21][22][23][24][25], but also reported in A 1-x R x MnO 3 ( A=Pr or La; B= Sr or Ca) bulk materials [26,27].…”
Section: Electron Diffraction Patterns and High-resolution Electron Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have many reports from domain-structure investigations in LCMO bulk and thin films [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] , superdislocations are seldom mentioned, and to our knowledge, were only observed in ordered alloys. 22 In this work, by means of using Bragg-diffraction contrast and high-resolution transmission electron microscopy, we investigated in detail the domains and dislocations of LCMO thin films deposited by pulsed laser on SrTiO 3 substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The colossal magnetoresistance (CMR) manganite materials La 1-x Ca x MnO 3 , especially their thin films, have been extensively explored in recent years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] because of their exciting potential practical applications and their interesting fundamental physics.…”
Section: Introductionmentioning
confidence: 99%